Prevalence of Novel Pedagogical Methods in the Radiology Education of Medical Students. Issue 12 (December 2022) - Martin, Jonathan G.; Fimbres, Denisse Cristina Porras; Wang, Sherry; Wang, Jennifer; Krupinski, Elizabeth; Frigini, L. Alexandre
Abstract : A literature search was performed to elucidate the various pedagogical methods used for radiology education in medical schools. After review, the evaluated methods were grouped into eight categories. US medical student radiology educators were then surveyed about the use of these eight categories of educational methods at their institution. Our findings demonstrate that although radiology education is pervasive and many data-driven novel approaches are gaining traction, there is significant heterogeneity in their use. There remains a lack of simulation, adaptive tutorials, and peer-to-peer learning, as well as a paucity of hands-on experience available for students, suggesting room for improvement in the delivery of radiology education. Abstract: Objectives: Radiology education is essential in medical school; however, developing an integrated and comprehensive curriculum remains a challenge. Many novel methods have been implemented with varying outcomes. In this study, the authors sought to examine published pedagogical methods of radiology instruction and query US academic faculty members on their current use within radiology education. Methods: A literature search for current and novel pedagogical methods of radiology instruction was performed and studies were assessed for positive educational outcomes. Educational approaches were grouped according to encountered themes. A survey was distributed to faculty members of the Alliance of Medical Student Educators in Radiology to ascertain the prevalence of these pedagogical methods in the radiology education of medical students. Results: The following themes were encountered: supplemental instruction of anatomy and pathology; radiology–clinical correlation electives; flipped classrooms; hands-on and simulation training; peer-to-peer learning; e-learning; adaptive tutorials; and asynchronous learning. Of the survey respondents, 90% reported that their institution offers a formal radiology clerkship. The majority of respondents reported the use of flipped classrooms (70%) and e-learning (78%); however, few reported offering hands-on clinical experiences (31%) and simulation-based training (36%). Only 5% reported use of adaptive tutorials. Conclusions: In the review of the literature, a combination of hands-on, case-based, team-based, and didactic training, in addition to other forms of active learning within an integrated curriculum, was found to be highly effective and preferred by students and faculty. Virtual and in-person learning incorporating modern technology was found to either increase knowledge and skills or yield similar outcomes as traditional in-person instruction. These methods are currently heterogeneously used across the US medical schools represented by survey respondents, with utilization ranging from 5% to 78%.